Spatial distribution of the potential risk for avocado wilting disease, caused by Phytophthora cinnamomi in the subregion of Montes de Maria, Colombia (2018)
Avocado wilting or root rot, caused by the oomycete Phytophthora cinnamomi Rands, is the most limiting disease of avocado crops around the world. Montes de Maria (MM) is the main producer region of avocado in the Colombian Caribbean. Avocado producing areas in MM are decreasing in an inverse trend compared with the increasing hectarage world and nation-wide. Decreasing hectarage in MM is associated with phytosanitary problems, specifically the avocado wilting caused by P. cinnamomi. Climate is one of the main abiotic factors determining spatial distribution of species. For plant-pathogens, environmental conditions determine host-colonization. Under this scenario, the aim of this study was to estimate the spatial distribution of the avocado root-rot risk in the subregion of Montes de Maria, Colombia. This estimation was based on data for the presence of shoot dieback, a characteristic, easily identifiable symptom of root rot caused by P. cinnamomi. This symptom exhibits a high correlation with disease incidence and severity. A Maxent model was used to estimate the spatial distribution of the risk, showing a high statistical validation (test AUC>0.9). This model identified areas with a high risk for occurrence of branch dieback and, consequently, root rot. Areas with a higher risk of root rot were found at the higher altitudes, with lower temperatures in the coldest trimester (BIO11 ~22°C), and in the warmest one (BIO10 ~24°C), with higher rainfall during the dry season (BIO17 - BIO14).